Characteristics and Source Regions of Slow Alfvénic Solar Wind Observed by Parker Solar Probe - Tamar Ervin; Kai Jaffarove; Samuel T. Badman; Jia Huang; Yeimy J. Rivera; Stuart D. Bale (The Astrophysical Journal)
Using a classification scheme for solar-wind type based on the heliocentric distance of the observation, we look at near-perihelion observations from Parker Solar Probe Encounters 4 to 14 to study the sources of the slow Alfvénic solar wind (SASW). Through Potential Field Source Surface (PFSS) modeling and ballistic mapping, we connect streams to their solar source and find that a primary population of SASW comes from low magnetic field strength regions (low- B _0 ), likely small coronal holes (CHs) and their overexpanded boundaries, while a second population of high field strength (high- B _0 ) seems to emerge from non-CH structures potentially through interchange reconnection with nearby open field lines. This low- B _0 SASW shows larger expansion than the fast solar wind (FSW) but similar mass flux, potentially indicating additional heating below the critical point, and emergence from a cooler structure, which could lead to slower wind emerging from CH-like structures. We show that this low- B _0 SASW shows stronger preferential acceleration of alpha particles (similar to the FSW) than the high- B _0 SASW, and that this is a velocity-dependent phenomenon as found in previous studies. To have additional confidence in our mapping results, we quantify the error on both the PFSS model and ballistic mapping and discuss how additional multipoint observations of plasma parameters and composition would allow us to better constrain our models and connect the solar wind to its source.